Boomeranging around Australia: Historical biogeography and population genomics of the anti‐equatorial fish Microcanthus strigatus (Teleostei: Microcanthidae). Issue 16 (1st August 2019) - Tea, Yi‐Kai; Van Der Wal, Cara; Ludt, William B.; Gill, Anthony C.; Lo, Nathan; Ho, Simon Y. W.
Abstract: The geographic distributions of marine fishes have been shaped by ancient vicariance and ongoing dispersal events. Some species exhibit anti‐equatorial distributions, inhabiting temperate regions on both sides of the tropics while being absent from equatorial latitudes. The perciform fish Microcanthus strigatus (the stripey) exhibits such a distribution with disjunct populations occurring in East Asia, Hawaii, Western Australia, and the southwest Pacific. Here, we examine the historical biogeography and evolutionary history of M. strigatus, based on more than 80 specimens sampled from the four major populations. We analysed 36 morphological characters, three mitochondrial markers, and two sets of 7, 120 and 12, 771 single‐nucleotide polymorphisms from the nuclear genome. Our results suggest that M. strigatus represents a cryptic species complex comprising at least two genetically distinct populations worthy of species‐level recognition, with one population exhibiting strong genetic structuring but with intermittent, historical gene flow. We provide evidence for a southwest Pacific origin for the ancestral Microcanthus and explain how past connectivity between these regions might have given rise to the relationships observed in present‐day marine fauna. Our ancestral range reconstructions and molecular‐clock analyses support a southwest Pacific centre of origin for Microcanthus, with subsequent colonization of Western Australia through the Bass Strait followed by transequatorial dispersals to the Northern Hemisphere during the Pleistocene. Our results detail an anti‐tropical dispersal pattern that is highly unusual and previously undocumented, thereby emphasizing the importance of integrative systematics in the evaluation of widespread species.